TRANSFORMASI PENANGANAN TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DI LPKA KLAS II TANJUNG PATI - Yenny Fitri Z; Nedi Rinaldi (Ensiklopedia Social Review, 2019)
Child-specific guidance institution (LPKA) class II Tanjung Pati was opened officially by the head region of west sumatera law and human rights ministry to replace child and woman’s prison class II B.The opening of LPKA is based on the law number 11 2012 about child crime justice as the change of the law number 3 1997 about child justice. The existence of this LPKA hoped to be able to actualize Transformation of handling child who has conflict with the law. The aim of this research is to know and to describe the difference of child guidance system at prison class II B with LPKA class II Tanjung Pati.and also explains about handicaps and efforts in overcoming handicaps of child guidance implementation at LPKA. The approach used in this research are juridical and empirical. Combining primary and secondary data which is achieved by doing field research analyzed by using qualitative analysis method. The changes of system at LPKA are nomenclature changes, the difference of child guidance approach, the difference of term for guided child, and the difference of guided child characteristics. The handicaps found by LPKA during child guidance implementation are un accomodated education of guided child, the minimum of people and local goverment’s care, and the existence of woman’s prison which is still united with LPKA. Many efforts have been done to overcome these handicaps, but still don’t show maximum results.